2019
DOI: 10.1111/vec.12816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous positive airway pressure on respiratory function in sedated foals

Abstract: Objective:To characterize the effects of continuous positive airway pressure (CPAP) delivered by a commercial human CPAP device on respiratory function in foals with pharmacologically induced respiratory suppression.Design: Prospective randomized, cross-over study comparing CPAP with spontaneous respiration and oxygen insufflation. Setting: University veterinary teaching hospital.Animals: Twelve foals born in consecutive seasons from a university teaching herd.Interventions: Foals were randomized to receive 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 25 publications
9
27
1
Order By: Relevance
“…Increased Vt represents a more efficient ventilation strategy than increased RR, as there is increased alveolar ventilation relative to ventilation of airway dead space, and decreased RR is likely to be associated with decreased work of breathing. Increased inspiratory pressure during biPAP was associated with increased PIF, and the adverse effects on PEF observed during CPAP in previous studies (13) were not observed in the current study, presumably due to the lower expiratory pressures during biPAP ventilation. As expected, increased FiO 2 was observed during mask administration of supplementary O 2 and during biPAP, so observed increases in arterial oxygenation likely reflect the steeper diffusion gradient resulting from these changes.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Increased Vt represents a more efficient ventilation strategy than increased RR, as there is increased alveolar ventilation relative to ventilation of airway dead space, and decreased RR is likely to be associated with decreased work of breathing. Increased inspiratory pressure during biPAP was associated with increased PIF, and the adverse effects on PEF observed during CPAP in previous studies (13) were not observed in the current study, presumably due to the lower expiratory pressures during biPAP ventilation. As expected, increased FiO 2 was observed during mask administration of supplementary O 2 and during biPAP, so observed increases in arterial oxygenation likely reflect the steeper diffusion gradient resulting from these changes.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have demonstrated that CPAP is associated with improved respiratory function in a number of veterinary species (912). CPAP has recently been shown to improve gas exchange in healthy foals with pharmacologically induced respiratory suppression (13), however hypercapnia was observed in treated foals in this study, and has been observed previously in anaesthetised horses during CPAP (10, 11, 14).…”
Section: Introductionsupporting
confidence: 46%
See 3 more Smart Citations